2014
DOI: 10.3390/molecules191117632
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phytochemical Synthesis, Chalcone Synthase Activity and Pharmaceutical Qualities of Sabah Snake Grass (Clinacanthus nutans L.) in Relation to Plant Age

Abstract: In the current study, changes in secondary metabolite synthesis and the pharmaceutical quality of sabah snake grass leaves and buds were considered in relation to plant age (1 month, 6 months, and 1 year old). The activity of the enzyme chalcone synthase (CHS, EC 2.3.1.74) was measured, as it is a key enzyme for flavonoid production. Significant differences in total flavonoid (TF) production were observed between the three plant growth periods and the different plant parts. The highest contents of TF (6.32 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 34 publications
(36 reference statements)
6
60
1
1
Order By: Relevance
“…Furthermore, the highest initial flavonoid content is attributed to young leaves, followed by young stems. Ghasemzadeh et al (2014) also confirmed that phenolic contet of C. nutans was higher in early growth stage compared with matured stages. But, these findings are not in conformity with those of Nor Qhairul Izzreen & Mohd Fadzelly (2013), who reported that C. sinensis (green tea) contains highest total flavonoids in shoots (35 mg rutin 100 g -1 ) followed by young (32 mg rutin 100 g -1 ) and matured leaves (21 mg rutin 100 g -1 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, the highest initial flavonoid content is attributed to young leaves, followed by young stems. Ghasemzadeh et al (2014) also confirmed that phenolic contet of C. nutans was higher in early growth stage compared with matured stages. But, these findings are not in conformity with those of Nor Qhairul Izzreen & Mohd Fadzelly (2013), who reported that C. sinensis (green tea) contains highest total flavonoids in shoots (35 mg rutin 100 g -1 ) followed by young (32 mg rutin 100 g -1 ) and matured leaves (21 mg rutin 100 g -1 ).…”
Section: Discussionsupporting
confidence: 71%
“…Rafat et al (2009) also reported similar findings from their study with A. paniculata. Ghasemzadeh et al (2014) on the other hand, recorded higher DPPH value in 1-year -old buds than in 6-month-old buds of C. nutans.…”
Section: Discussionmentioning
confidence: 79%
“…The environmental conditions. 5 such as sunlight condition, 10 the marurity part of plant and differences part of plant could be a factor to differences type and quantity secondary metabolites.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…condition, air pressure and temperature. 10 Beside that, the maturity part of plant could be a factor to differences type and quantity secondary metabolites. 11,12 Antioxidants are one of the components needed in the body, to counteract free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The ovary is packed into two cells and each cell contains two ovules [9] . Phytochemical analysis has shown that C. nutans contains several kinds of clinamide derivatives [10] , alkaloids [11] , chlorophyll [12] , flavonoids [13] , phenolic compounds [14] .…”
mentioning
confidence: 99%